Pendidikan Agama Islam: Perspektif Teologis, Sosial, dan Kemanusiaan - Dian Sandi Utama; Tobroni Tobroni; Faridi Faridi (Jurnal Syntax Admiration, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping the character of students with the Rahmatan lil 'Alamin paradigm which involves theological, social, and humanitarian dimensions. This research aims to explore the integration of Rahmatan lil 'Alamin values in PAI through this approach. The method used is literature research with the main sources of Qur'an verses, books, and relevant scientific articles. The results of the study show that the Rahmatan lil 'Alamin paradigm can be applied through the development of curriculum, teaching materials, and teaching methods that emphasize compassion, tolerance, social justice, and respect for diversity. PAI plays a role not only in shaping religious students, but also humanists, with a global awareness of the role of Islam in world peace. This study makes a significant contribution to the development of a holistic approach to PAI that is relevant to current social and global challenges.